Upaya Meningkatkan Kemampuan Menghitung melalui Media Konkret Papan Penjumlahan dan Pengurangan (Panjurang) - Rahmawati, Rahmawati; Tahir, Muhammad; Khaerudin, Khaerudin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the arithmetic skills of first-grade students at SDN 23 Mataram through the use of concrete media called the Panjurang Board (Addition and Subtraction Board). The method used was Classroom Action Research (CAR), consisting of a pre-cycle and two cycles. The research subjects were 14 students. Data were collected through observation and learning outcome tests. The pre-cycle results showed that most students had difficulty performing calculations, with 28.57% categorized as "not yet able." In Cycle I, after using the Panjurang media, there was an improvement, with the number of students in the "able" and "very able" categories increasing to 50%. By Cycle II, all students had reached the "able" category or higher, with 35.71% categorized as "very able." This study demonstrates that the Panjurang media is effective in enhancing students’ arithmetic skills. The media helps students understand arithmetic operations in a more concrete and interactive way. Therefore, the Panjurang Board can serve as an alternative instructional tool for teaching mathematics in elementary schools.